Short-term effects of retinoic acid on the proliferation of SH-SY5Y cells via mitophagy and apoptosis: Retinoic acid, glioblastoma and mitophagy - Aydin, Dilara; Öner, Çağrı; Aslan Öztürk, Senem; Çolak, Ertuğrul (Cellular and Molecular Biology, 2024)
Neuroblastoma shows the highest lethality in childhood and has poor prognosis at high grade. Our objectives included determining how retinoic acid affected the growth of neuroblastoma cells and the relationship between chemicals unique to neurons and cell death processes like apoptosis and mitophagy. The 50% inhibitory concentration of retinoic acid on SH-SY5Y neuroblastoma cells was determined at the 24th, 48th and 72nd hours. At the optimal concentration of retinoic acid on SH-SY5Y cells, Ki-67, cytochrome C, HIF-1α, Parkin, α-synuclein, DJ-1 and tyrosine β- hydroxylase gene expressions were determined by using RT-PCR. Tyrosine β-hydroxylase protein expression was assessed by ELISA. The optimal time and concentration for retinoic acid in SH-SY5Y cells was 10 μM at the 24th hour. The decreased gene expressions of Ki-67, α-synuclein, DJ-1 and tyrosine β-hydroxylase were observed while Cyt C, HIF-1α and Parkin gene expressions were upregulated (p<0.001). Tyrosine β-hydroxylase protein expression increased at the 24th and 72nd hours although it decreased at the 48th hour (p<0.001). Retinoic acid has short-term effect on the proliferation of SH-SY5Y neuroblastoma cells. It was observed that short-term retinoic acid treatment improved neurodegeneration parameters, but it decreased the proliferation by inducing mitophagy and apoptosis of SH-SY5Y neuroblastoma cells.